Exploring indices of disordered eating literacy in male and female athletes: Knowledge gaps and lay beliefs as predictors of attitudes toward help-seeking - McArdle, S.; Moore, P. (Journal of Clinical Sport Psychology, 2013)
The aim of this pilot study was to explore disordered eating (DE) literacy in male and female athletes and to examine whether any gender differences were present. A related aim was to examine the moderating effect of gender on the relationship between indices of DE literacy and attitudes toward help-seeking for DE. A nonclinical sample of 133 (37% male) athletes from a variety of sports and competitive levels were recruited to complete an online questionnaire addressing a range of topics linked to DE literacy. Chi-square analysis indicated no significant gender differences on indicators of DE literacy. Findings from the survey revealed a number of beliefs conducive to low or inappropriate help-seeking for DE. The results highlight the importance of exploring DE literacy in athletes to develop more targeted interventions for this specific population.